1971
DOI: 10.1111/j.1471-0528.1971.tb00198.x
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of the Changes in the Continuous Fetal Heart Rate in the First Stage of Labour

Abstract: AND SummaryA comparison between data derived from changes in fetal heart rate and p H of fetal blood in 279 high-risk patients is described. 'The incidence of fetal acidosis was low when the continuous record of FHR showed good beat-to-beat variation in rhythm and no slowing during uterine contractions. The incidence of fetal acidosis accompanying fetal tachycardia or bradycardia was low if the rate remained unaltered during contractions. Decelerations of fetal heart rate accompanied by baseline tachycardia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
3

Year Published

1976
1976
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(48 citation statements)
references
References 12 publications
2
43
0
3
Order By: Relevance
“…The relationship between minimal or undetectable FHR variability in the presence of late decelerations or variable decelerations, and the presence of acidemia and/or a depressed neonate Eight papers were identified which included a total of 588 appropriate patients, all of which had at most minimal FHR variability and decelerations [7][8][9][10][15][16][17][18]]. We were not always able to distinguish between undetectable or minimal variability in the published data because they were sometimes grouped together.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between minimal or undetectable FHR variability in the presence of late decelerations or variable decelerations, and the presence of acidemia and/or a depressed neonate Eight papers were identified which included a total of 588 appropriate patients, all of which had at most minimal FHR variability and decelerations [7][8][9][10][15][16][17][18]]. We were not always able to distinguish between undetectable or minimal variability in the published data because they were sometimes grouped together.…”
Section: Resultsmentioning
confidence: 99%
“…Five relevant publications were identified where FHR pattern descriptions, and fetal blood gases and acid-base state from scalp samples or Apgar scores were available [7][8][9][10][11]. All of the tracings used had moderate FHR variability, and we did not exclude series where there were concomitant decelerations or bradycardias.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies correlating different CTG abnormalities to fetal status had small study populations [3,6,14] , or used neonatal outcome measures, e.g., umbilical blood gases and cerebral palsy as outcomes [18,35] . Umbilical blood gases are influenced by the action taken and time interval to delivery and intrapartum acidemia is only a minor contribution to cerebral palsy.…”
Section: Introductionmentioning
confidence: 99%
“…In 1971 a comparison was made between FHR changes and pH of foetal blood. Decelerations and a loss of beat-to-beat variability appeared to be associated with foetal acidosis and therefore foetal asphyxia [51]. Huovinen et al [6] found a higher incidence of FHR changes in the supine position when compared to lateral position.…”
Section: Aetiology Of Fhr Changesmentioning
confidence: 96%